If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(u + 7) = -18 Reorder the terms: -3(7 + u) = -18 (7 * -3 + u * -3) = -18 (-21 + -3u) = -18 Solving -21 + -3u = -18 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -3u = -18 + 21 Combine like terms: -21 + 21 = 0 0 + -3u = -18 + 21 -3u = -18 + 21 Combine like terms: -18 + 21 = 3 -3u = 3 Divide each side by '-3'. u = -1 Simplifying u = -1
| 6a+42-2a=50 | | 15=19+2(9+18) | | y=(1-x)2 | | 15u-42(8u)= | | 142+x=64+3x | | 5(r-10)=2(r-4)-6 | | 5+35=125 | | 12v-8(8v)= | | 3b+11=50 | | 5x+4y=1.5 | | 2x+(45-6x)=17 | | x=43x*2 | | 1.2c+5=1.4 | | 120X=4000-160X | | -7+5y=-37 | | x^4+81y^4=165-xy | | 2u+8=2 | | 4100=4000c-500 | | 16-6(-3x+4)=-2 | | 2x-9=6x+4 | | c/5-4=3 | | 38+x=2x+6x-2 | | 8*w=52 | | 16-6(-3x+4)=2 | | 31-4x=5x+19 | | 22=8x+1-5X | | x^2+17x+31=4x-5 | | 24+-2a+3=7a | | 5(3-x)=-(1+x) | | x^2+x-18=2 | | -24=-4(k+3) | | 7h-7=17+4h |